2003
DOI: 10.1097/01.ju.0000084297.43710.e9
|View full text |Cite
|
Sign up to set email alerts
|

Association Between A C/A Single Nucleotide Polymorphism of the E-Cadherin Gene Promoter and Transitional Cell Carcinoma of the Bladder

Abstract: The -160 C/A single nucleotide polymorphism of the E-cadherin gene promoter is associated with TCCB. This single nucleotide polymorphism may serve as a prognostic marker of TCCB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 11 publications
1
20
1
Order By: Relevance
“…Five studies [53][57], including two updated reports [54], [57], detected the -160C/A polymorphism in urothelial cancer patients, which involved 1,064 cases and 1,124 controls. Overall, the meta-analysis showed that the -160A carriers had a significantly increased risk of developing urothelial cancer (OR = 1.70, 95% CI = 1.11–2.61), and significant heterogeneity was found among the five studies ( Q  = 20.37, P  = 0.0004, I 2  = 80%).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies [53][57], including two updated reports [54], [57], detected the -160C/A polymorphism in urothelial cancer patients, which involved 1,064 cases and 1,124 controls. Overall, the meta-analysis showed that the -160A carriers had a significantly increased risk of developing urothelial cancer (OR = 1.70, 95% CI = 1.11–2.61), and significant heterogeneity was found among the five studies ( Q  = 20.37, P  = 0.0004, I 2  = 80%).…”
Section: Resultsmentioning
confidence: 99%
“…It has been hypothesized that the promoter region of the CDH1 gene is responsible for interindividual variation in the production of CDH1 and in turn leads to individual susceptibility to various cancers (Chik et al, 2011). Many previous genetic studies have also suggested that CDH1 promoter polymorphism -160C/A may play an important role in bladder carcinogenesis (Tsukino et al, 2003;Zhang et al, 2003;Kiemeney et al, 2006;Ma et al, 2008). There is a compelling biological rationale for using CDH1 promoter polymorphism and DNA methylation to hinder tumor recurrence, progression, and development of metastases in bladder cancer.…”
Section: Discussionmentioning
confidence: 96%
“…CDH1-160 SNPs reveals conflicting results. For example, Verhage et al [31] and Zhang et al [32] reported that the A allele carriers had an increased risk of prostate and bladder cancer, respectively, while Tsukino et al [33] showed that CDH1-160 SNPs are not related to the incidence and progression of prostate cancer in the Japanese population. Likewise, in the current HCC results and previous studies on colorectal [30] or gastric cancer [34] reveal that CDH1-160 SNPs may not be genetic markers to identify individuals at higher risk for these diseases.…”
Section: Discussionmentioning
confidence: 97%